Ferrofluid-based shape-controllable and fast-responsive micro-pumping and valving actuation - Tang, Jiawei; Luk, Patrick Chi-Kwong (IEEE, 2022)
Micro-pumping and valving based on ferrofluid is a promising research area that offers novel solutions in many potential engineering and biomedical applications. In this paper, a novel electromagnetic actuated valve design based on ferrofluid action is presented. To date, traditional mechanical pumps and valves is replete with limiting features such as low on-off frequency limit, contact wear losses, and bulky size. However, due to the superparamagnetism and the high magnetic susceptibility of the ferromagnetic nanoparticles, ferrofluid can be actuated by magnetic field to perform fast-responsive, shape-controllable and small-scale valving actions. In this study, finite element models are built to analyze various design parameters including valve shape, valve dimensions, electromagnetic characteristic of ferrofluid and applied magnetic fields. An electromagnetic actuated ferrofluid valve is then designed and implemented. The valves are tested with switching frequency up to 250 Hz, and the valve’s diameter can be scaled down to 1 mm and beyond.
Keywords: Ferrofluid; micro-valve; micro-pump; electro-magnetic actuation